A Study to Assess the Impact of Online Mode of Education on the Learning of B. Sc. Nursing Students of Kashmir - Siraj, Syed Shahid; Arifa, Syed (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2022)
Due to the emergence of COVID-19, all the educational institutions were shut globally and the mode of teaching and learning changed from in person classroom mode to online mode of education by using different virtual interfaces of internet. The objective of this study is to review the impact of online education on the learning of B. Sc nursing students of two nursing colleges of Kashmir. 60 students from two nursing colleges of Kashmir were selected using a purposive sampling technique. A web-based questionnaire was used for data collection. The connection of online instruction with creativity among understudies, inspiration of understudies towards learning, and execution of understudies was assessed. Results recommended that some significant endeavors should be made to keep on further developing on the web innovation that cultivates dynamic learning openings for understudies through online training. It is prescribed to have better distance learning climate or top of the line online study halls that can detect a student's inspiration even out and react adaptively.